Spatial analysis and correlation study of risk factors of filariasis incidents in Southeast Sulawesi in 2024 - Sabrina Wahyuni Meyitia; Hariati Lestari; Listy Handayani (PT WIM Solusi Prima, 2026)
Filariasis is a reemerging disease that remains a public health issue in Indonesia, including in Southeast Sulawesi Province. The purpose of this study was to analyze the relationship and spatial distribution of risk factors for filariasis incidence in Southeast Sulawesi in 2024. The type of research used was descriptive observational with population observation units based on ecological study design. The population and sample of the study included data on filariasis cases, regional altitude, population density, and socioeconomic levels in Southeast Sulawesi in 2024, which were collected using a total sampling technique. Data collection used a documentation study method with secondary data from the Central Statistics Agency (BPS) of Southeast Sulawesi Province in 2024 and the Southeast Sulawesi Provincial Health Office in 2024. The analysis was carried out using univariate analysis, bivariate analysis, Shapiro–Wilk normality test, Spearman correlation test, and spatial analysis. The results showed that gender was significantly correlated with filariasis incidence (r=0.990; p=0.000). Meanwhile, altitude (r=0.470; p=0.057), population density (r=-0.040; p=0.878), and socioeconomic level (r=-0.112; p=0.669) did not show a significant correlation. The study concluded that the incidence of filariasis in Southeast Sulawesi in 2024 was significantly correlated with gender, while altitude, population density, and socioeconomic level were not significantly correlated. These findings are expected to provide a basis for planning more targeted filariasis control efforts.